TINJAUAN TENTANG PELAKSANAAN EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MK NO.18/PUU-XVII/2019 TENTANG OBJEK JAMINAN FIDUSIA - sari, Ayu Frizcha; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Fiduciary as one of the guarantees is an element of bank credit security, which was born preceded by a bank credit agreement. Banks as fiduciary creditors have fiduciary interests based on special guarantee agreements. A fiduciary guarantee agreement is an agreement that arises because of a bank credit agreement. If the debtor customer defaults, The occurrence of this case led to the Constitutional Court Decision. In the decision of the Mahmakah of the Constitution Number 18 / PUUXVII / 2019 dated January 6, 2020, the Constitutional Court stated that the recipient of fiduciary rights or creditors may not carry out the execution by themselves but must submit a request for execution to the district court, against fiduciary guarantees where there is no agreement on injury promise (default) and the debtor objecting to voluntarily hand over the object which is a fiduciary guarantee This research. This type of research is sociological legal research. Sociological legal research is research that is carried out directly in the location or in the field to obtain data to provide a complete and clear picture of the problem under study. In this study the author focuses on the effectiveness of the law in society. Talking about the effectiveness of the law means talking about the power of the law in regulating and / or compelling to obey the law. As seen from its nature, this research is descriptive in nature, which provides an explanation of a description of the situation, atmosphere and conditions regarding fiduciary security. The results of this study are to determine the implications of the Constitutional Court Decision Number 18 / PUU-XVII / 2019 concerning the Implementation of Fiduciary Guarantee The Constitutional Court decision provides clarity on the phrase of default in the Elucidation of Article 15 paragraph 2 of the Fiduciary Guarantee Law. Such as the forced withdrawal of a customer's vehicle is a breach of the promise of the agreement that has been agreed. Execution of the Fiduciary Guarantee Object After the Constitutional Court Decision Number 18 / PUU-XVII / 2019 Regarding the Object of the Fiduciary Guarantee, the creditor has the right to carry out the execution and sale of the object of guarantee under his own power. There is no justice for customers by not being enforced according to the Decision of the Constitutional Court Number 18 / PUU-XVII / 2019 concerning Fiduciary Guarantee.Keywords : Execution - Object of Fiduciary Guarantee - Constitutional Court Decision